menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Which equation is modeled below? -x+ 1 = 2x+ 3 X+(-1) = 2x+3 X+(-1) = 3x+2 -2x = 2x+3
asked
Jan 14, 2021
108k
views
5
votes
Which equation is modeled below?
-x+ 1 = 2x+ 3
X+(-1) = 2x+3
X+(-1) = 3x+2
-2x = 2x+3
Mathematics
high-school
Tyler Wall
asked
by
Tyler Wall
4.7k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
2
Answers
1
vote
Answer:
A
Explanation:
ArthurGuy
answered
Jan 16, 2021
by
ArthurGuy
4.5k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
5
votes
Answer:
Explanation:
First one
IttayD
answered
Jan 20, 2021
by
IttayD
6.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.7m
questions
7.4m
answers
Other Questions
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Can someone help me with 5??? ASAP?
Solve for h 3h=7(2/7-3/7h)-10
1/7 + 3/14 equivalent fractions
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org